SEMANTIC FIELD OF THE VERBALIZER "GUEST" IN ENGLISH (American Journal of Pedagogical and Educational Research, 2023)
This article examines the semantic field of the verbalizer "guest" in the English language. The author of the article believes that the English people associate with the concept of "hospitality" such notions and concepts as: hospitality, warm welcome, an invitation to visit, a treat, a national dish, observance of rituals. Based on the given associative series and characteristic features of the verbalizer "guest", we chose the following elements of the conceptual field: hospitable host, welcoming guests, reception, feast.